REGIONAL DEVELOPMENT'S PERSPECTIVES IN EUROPE - Mihai, OPRESCU (Strategii Manageriale)
Increasing regions' importance in Europe represents a striking phenomenon in the last years. Regional development is an evolving process that aims at reducing socio-economic disparities at the level of a certain territory, while boosting its potential. One of the European Union objectives is to sustain balanced and sustainable economic and social progress, strengthening economic and social cohesion of member countries. An important role in this process is played by the regions, which are considered closer to the citizens. In European states, the forms of regionalization correspond to different administrative and political realities existing in those countries. Models applied varies by the powers given to regional authorities, involved institutions, the degree of decentralization, being several types of regionalization.